1995
DOI: 10.1007/bf00192633
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone structure in patients with primary hyperparathyroidism

Abstract: To evaluate the effects of increased parathyroid hormone (PTH)-secretion on trabecular bone structure in patients with primary hyperparathyroidism (PHPT) we have analysed iliac crest biopsies from 84 patients (38 male, 46 female, age 20-85 years) with surgically proven PHPT by using quantitative histomorphometry. As there might be an influence of age or sex, subjects were divided into 4 subgroups according to age (younger than 50 years, older than 50 years) and sex. Eighty four age and sex matched autopsy case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
2
14
3
Order By: Relevance
“…We have reported an increase in wall width as the underlying mechanism of conservation of cancellous bone in this disease, 68 confirming previous findings. 69 However, in our study, greater wall width was associated with thinner trabecular plates, 62 in contrast with thicker plates observed in the Vogel et al study. 69 The reason for this discrepancy is not clear and, at present, we have no direct information on whether the greater final amount of bone is the result of a positive bone balance in each remodeling unit, because in neither study was depth of erosion measured.…”
Section: Mechanism Of Maintenance Of Cancellous Bone Volume and Struccontrasting
confidence: 62%
See 1 more Smart Citation
“…We have reported an increase in wall width as the underlying mechanism of conservation of cancellous bone in this disease, 68 confirming previous findings. 69 However, in our study, greater wall width was associated with thinner trabecular plates, 62 in contrast with thicker plates observed in the Vogel et al study. 69 The reason for this discrepancy is not clear and, at present, we have no direct information on whether the greater final amount of bone is the result of a positive bone balance in each remodeling unit, because in neither study was depth of erosion measured.…”
Section: Mechanism Of Maintenance Of Cancellous Bone Volume and Struccontrasting
confidence: 62%
“…69 However, in our study, greater wall width was associated with thinner trabecular plates, 62 in contrast with thicker plates observed in the Vogel et al study. 69 The reason for this discrepancy is not clear and, at present, we have no direct information on whether the greater final amount of bone is the result of a positive bone balance in each remodeling unit, because in neither study was depth of erosion measured. 68,69 Furthermore, in our study, we found that the active formation period was longer in hyperparathyroid than in normal women.…”
Section: Mechanism Of Maintenance Of Cancellous Bone Volume and Struccontrasting
confidence: 62%
“…Several authors have described a decrease in the BV/TV with increasing age. 15,17,20,21 In all of these studies the age span was from young to very old and probably explains the disagreement between these reports and our findings.…”
Section: Discussioncontrasting
confidence: 56%
“…The architectural properties of bone have been explored in relation to age, aiming mostly at changes related to ageing, and using almost exclusively 2D analytical techniques. [14][15][16][17][18][19][20][21] The relationship between the architectural and the mechanical properties of bone has been studied by several authors, using both 2D 2,6,[14][15][16][17]19,[21][22][23][24] and 3D…”
Section: Discussionmentioning
confidence: 99%
“…Most centres utilising bilateral neck explorations limit the use of biopsies of overtly normal-sized glands in order to decrease the risks of postoperative hypoparathyroidism (Lafferty & Hubay 1989). Unilateral neck explorations have been utilised to treat patients with single parathyroid adenoma (Tibblin et al 1982, Welsh et al 1990, Robertson et a1.1996, Vogel et al 1998, and local tumour removal has been introduced more recently (Miccoli et al 1998A,B, Norman et al 1998. Percutaneous injection of ethanol into parathyroid tumours by ultrasonic guidance might be utilised in selected cases unsuitable for surgery (Karstrup et al 1993, Verges et al 1993).…”
Section: Parathyroid Surgerymentioning
confidence: 99%